Significance of Postprandial Insulin and Triglycerides to Evaluate the Metabolic Response of Composite Meals Differing in Nutrient Composition – A Randomized Cross-Over Trial - Thota, Rohith N.; Moughan, Paul J.; Singh, Harjinder; Garg, Manohar L. (Frontiers in Nutrition, 2022)
ABSTRACT Background and aims: GlucoTRIG, based on postprandial plasma insulin and triglyceride concentrations, has been recently developed as a novel index to determine the postprandial metabolic response to the meals. This study aimed to test GlucoTRIG as a measure for ranking composite meals for their metabolic effects. Methods: In a randomized cross-over trial, healthy adult volunteers (both males and females; n=10 for each meal) consumed three isocaloric test (2000kj) test meals (meal1, meal2, meal3) of varying macronutrient composition. Postmeal consumption, venous blood samples were collected to determine plasma insulin and plasma triglycerides for estimating the GlucoTRIG value using (Triglycerides180min x Insulin180min) - (Triglycerides0min x Insulin0min). Results: The GlucoTRIG values differed significantly (p=0.0085) across meals. The statistical significance remains even after adjusting for confounding variables such as baseline diet, insulin and triglycerides. The meal (M3) with a high fibre, low total fat content and containing less refined foods (fruits, beans, vegetables, plain yoghurt) exhibited a significantly (p=0.007) lower GlucoTRIG value (10 ± 7.7) compared to the other two meals, M1 (77 ± 19.8) and M2 (38 ± 12.1) which contained low processed foods, and were relatively high in fat and low in fibre meals. No statistically significant differences were observed between M1 and M2 meal. Conclusions: GlucoTRIG is a physiologically based index that may be useful to rank composite meals for reducing the risk of metabolic diseases. Further research focusing on the application of GlucoTRIG™ to foods, meals and diets is warranted.